2013
DOI: 10.7554/elife.00306
|View full text |Cite
|
Sign up to set email alerts
|

Time line of redox events in aging postmitotic cells

Abstract: The precise roles that oxidants play in lifespan and aging are still unknown. Here, we report the discovery that chronologically aging yeast cells undergo a sudden redox collapse, which affects over 80% of identified thiol-containing proteins. We present evidence that this redox collapse is not triggered by an increase in endogenous oxidants as would have been postulated by the free radical theory of aging. Instead it appears to be instigated by a substantial drop in cellular NADPH, which normally provides the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 45 publications
4
109
0
Order By: Relevance
“…It was found that the yeast cells underwent a significant increase in global oxidation (i.e. ϳ80% of the 300 proteins) several days before they died (40). A similar phenomenon was also observed during the lifespan of C. elegans, as the aged worms had significantly more oxidized protein thiols than young adults (41).…”
Section: The Expanding Landscape Of the Thiol Redox Proteomementioning
confidence: 55%
See 1 more Smart Citation
“…It was found that the yeast cells underwent a significant increase in global oxidation (i.e. ϳ80% of the 300 proteins) several days before they died (40). A similar phenomenon was also observed during the lifespan of C. elegans, as the aged worms had significantly more oxidized protein thiols than young adults (41).…”
Section: The Expanding Landscape Of the Thiol Redox Proteomementioning
confidence: 55%
“…These studies established a clear connection between the thiol oxidation statues and aging in S. cerevisiae and C.elegans (40,41). It was found that the yeast cells underwent a significant increase in global oxidation (i.e.…”
Section: The Expanding Landscape Of the Thiol Redox Proteomementioning
confidence: 85%
“…In the past, formations of cysteine S-sulphenic acids on proteins were detected indirectly, through measurement of cysteine reactivities toward hydrogen peroxide (H 2 O 2 ). Accordingly, proteomic techniques for large-scale redox profiling of cysteine oxidative modifications employed indirect analyses based on differential labeling of protein thiols 1625 . These techniques rely on high concentrations of thiol alkylating reagents, which may react with protein S-sulphenic acids as well 26, 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that levels of NADPH and NAD + decline upon yeast aging, but NADPH levels are maintained when yeast cells are starved [65][67]. Decline in NAD + levels with aging were also reported in mice [68].…”
Section: Resultsmentioning
confidence: 99%